MIM3: Methodology of Innovation Management - Alfaro Paredes, Emigdio Antonio (CENTRUM Publishing, 2015)
The purpose of the study was to develop a methodological proposal for improving the management of the innovation maturity until the level 3 of the Integrated Innovation Maturity Model (I2MM), considering an integrated methodological approach which includes the good management practices of the following management areas: (a) strategic management, (b) project management, (c) innovation models and innovation methods, (d) standards for innovation management, (e) knowledge management, and (f) financial management. As result, MIM3, the Methodology of Innovation Management for obtaining the level 3 of the I2MM in the organizations, is presented.
Keywords: Innovation Management; Innovation Maturity; Methodology; Project Management; Innovation Standards; http://purl.org/pe-repo/ocde/ford#5.02.04